2005
DOI: 10.1182/blood-2004-09-3728
|View full text |Cite
|
Sign up to set email alerts
|

Use of glycosylated recombinant human G-CSF (lenograstim) during and/or after induction chemotherapy in patients 61 years of age and older with acute myeloid leukemia: final results of AML-13, a randomized phase-3 study

Abstract: The role of glycosylated recombinant human granulocyte colony-stimulating factor (G-CSF) in the induction treatment of older adults with acute myeloid leukemia (AML) is still uncertain. In this trial, a total of 722 patients with newly diagnosed AML, median age 68 years, were randomized into 4 treatment arms: (A) no G-CSF; (B) G-CSF during chemotherapy; (C) G-CSF after chemotherapy until day 28 or recovery of polymorphonuclear leukocytes; and (D) G-CSF during and after chemotherapy. The complete remission (CR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
107
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 42 publications
5
107
1
Order By: Relevance
“…The schedule of administration seems important with a better benefit when repeating priming during all consolidation chemotherapy courses, instead of a unique sequence of administration during induction chemotherapy. 16 It appeared in our study that there was a potentiation of GM-CSF priming with the theoretical effect of TSC on cell cycle more than only on the cytotoxic efficacy of cytarabine. Indeed, a significant difference in terms of CR was initially observed after the first course of induction chemotherapy, 5 and a significant difference between GM-CSF and no GM-CSF was also noted in terms of EFS among patients receiving the ALFA-9000 TSC consolidation course, while there were no differences for those randomized in the CALGB-like, high-dose cytarabine consolidation study arm.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The schedule of administration seems important with a better benefit when repeating priming during all consolidation chemotherapy courses, instead of a unique sequence of administration during induction chemotherapy. 16 It appeared in our study that there was a potentiation of GM-CSF priming with the theoretical effect of TSC on cell cycle more than only on the cytotoxic efficacy of cytarabine. Indeed, a significant difference in terms of CR was initially observed after the first course of induction chemotherapy, 5 and a significant difference between GM-CSF and no GM-CSF was also noted in terms of EFS among patients receiving the ALFA-9000 TSC consolidation course, while there were no differences for those randomized in the CALGB-like, high-dose cytarabine consolidation study arm.…”
Section: Discussionmentioning
confidence: 57%
“…16 The reasons for these Figure 3. Event-free survival (EFS) according to the assigned treatment (GM-CSF vs no GM-CSF) and the risk groups are depicted.…”
Section: Discussionmentioning
confidence: 99%
“…Non-haematological adverse effects in the first induction course with AVG therapy AVG regimen regarding the degree of mylosuppression (data was not shown). Several studies about the role of G-CSF during and/or after induction therapy were initiated, but no conclusion could be made in this regard [12,21,22]. It is possible that the priming effect with G-CSF is different between intensive regimens and low dose regimens.…”
Section: Discussionmentioning
confidence: 99%
“…With extensive clinical use, G-CSF and GM-CSF have been found to be safe and without an increase in mortality in patients undergoing induction therapy for AML. [7][8][9] The administration of G-CSF to patients with early myelodysplastic syndrome has not been shown to increase the risk of leukemic transformation. 12 Lessons from aplastic anemia and severe chronic neutropenia Karyotypic abnormalities involving chromosome 7 produce the most adverse outcomes in patients with AML and MDS.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The majority of controlled studies have shown that overall survivals for patients with leukemia or BMT treated with G-CSF have not significantly differed from control and that regulatory approval has resulted in the widespread use of G-CSF. [7][8][9] Filgrastim in myeloid malignancies The risk of leukemogenesis has been a concern with the use of filgrastim because it can induce the release of immature myeloid precursors into the circulation. Myeloid leukemic cells may express G-CSF and/or GM-CSF receptors.…”
Section: Introductionmentioning
confidence: 99%